Curricular Integration of University Extension: Implementation, Perspectives, and Challenges in the Nursing and Society Course - Ferreira e Silva, Priscilla; Ribeiro de Castro Soares, Magda; Stofel Souza e Dutra, Sulamita Victoria (Guará Journal, 2025)
This study addresses the integration of university extension into the curriculum of the course “Nursing and Society,” implemented since 2022. Objectives: to broaden the debate on the curricularization of extension and its inclusion in the undergraduate nursing program at Ufes; to describe the experience of implementing and executing the extension curricularization and to list the perspectives and challenges of these extension practices. This is a descriptive study developed from 2022 to 2024, through health education carried out in elementary schools and a foster home in Vitória/ES, targeting children, pre-adolescents, and adolescents aged 4 to 15. The educational topics covered included personal hygiene, prevention of Pediculosis and its treatment, tuberculosis, leprosy, human parasites, and healthy eating. Results: 150 nursing undergraduates participated in extension activities, with direct (in-locus) involvement of 770 students from the municipal school system, in addition to the participation of pedagogues, school principals, and other health workers from the Maruípe and Jardim da Penha health units, teaching assistants, and graduate students. It is concluded that the 2020 Pedagogical Political Project of the Ufes Nursing Program showed significant advances in the curricularization of extension, enabling students to experience extension activities from the first semester of the course.